WEDDING ORGANIZER MARKETING COMMUNICATION STRATEGY @NGANTENAN.YUK THROUGH INSTAGRAM SOCIAL MEDIA - Khalifah Althaf Naufaliza Repinda Putra; Noviawan Rasyid Ohorella; Edy Prihantoro (Journal of Digital Media Communication, 2022)
This study aims to determine the marketing communication strategy of Wedding Organizer @Ngantenan.Yuk through Instagram social media. With the Instagram social media Wedding Organizer @Ngantenan. Let's do marketing and promotion. Marketing and advancements made by Wedding Organizer @Ngantenan.Yuk are posting photos and videos of client weddings and information about weddings through Instagram. The research method used in this study is a qualitative descriptive method. Primary data is from information obtained from interviews with several informants. In comparison, secondary data is in the form of data obtained from books and other sources. The theory used in scientific writing research is New Media. Data collection techniques used are observation, interviews, and documentation. Based on the research results, the marketing communication strategy carried out by the Wedding Organizer @Ngantenan.Yuk was considered very good and appropriate. The marketing communication strategy carried out by Wedding Organizer @Ngantenan.Yuk is through Instagram social media by posting photos and videos of the client's wedding. Therefore, Wedding Organizer @Ngantenan.Yuk utilizes Instagram social media as a promotional tool to create the desired target. The advice that researchers can give is to be more consistent in marketing their services on the Wedding Organizer Instagram account @Ngantenan.Yuk to attract the attention of clients and face competition from other Wedding Organizers.